Image of Shesashayi Vishnu - Temples of India Project Team (Jio Institute, 2024)
Despite the predominantly Shaiva atmosphere of the Harshnath Temple Complex, there were once multiple Vaishnava temples on the hill. This particular image of Shesashayi Vishnu, or Vishnu reclining on the serpent. It was obtained from Harsha Hill and is now housed in the Government Museum, Sikar. Lord Shesa, likely served as the main cultic image inside a now lost Vaishnava shrine. Atop the image are representations of the nine planets, while Vishnu is attended to by Lakshmi at his feet. Three ayudhapurusa, personification of his weapons, are placed behind him. The reclining Vishnu adheres to standard iconography, wearing a kirita-mukuta, a malavanamala and four arms. In his upper left hand, he holds a chakra, while his upper right hand wields a mace, which also supports his head. His lower right-hand holds a flower, while the left lower hand is broken.